Electrospun gelatin/PCL and collagen/PLCL scaffolds for vascular tissue engineering - Fu W (Dove Medical Press, 2014)
Wei Fu,1,2,* Zhenling Liu,1,* Bei Feng,1,2 Renjie Hu,1 Xiaomin He,1 Hao Wang,1 Meng Yin,1 Huimin Huang,1 Haibo Zhang,1 Wei Wang11Department of Pediatric Cardiothoracic Surgery, 2Institute of Pediatric Translational Medicine, Shanghai Children's Medical Center, Shanghai Jiao Tong University School of Medicine, Shanghai, People's Republic of China*These authors contributed equally to this workAbstract: Electrospun hybrid nanofibers prepared using combinations of natural and synthetic polymers have been widely investigated in cardiovascular tissue engineering. In this study, electrospun gelatin/polycaprolactone (PCL) and collagen/poly(l-lactic acid-co-ε-caprolactone) (PLCL) scaffolds were successfully produced. Scanning electron micrographs showed that fibers of both membranes were smooth and homogeneous. Water contact angle measurements further demonstrated that both scaffolds were hydrophilic. To determine cell attachment and migration on the scaffolds, both hybrid scaffolds were seeded with human umbilical arterial smooth muscle cells. Scanning electron micrographs and MTT assays showed that the cells grew and proliferated well on both hybrid scaffolds. Gross observation of the transplanted scaffolds revealed that the engineered collagen/PLCL scaffolds were smoother and brighter than the gelatin/PCL scaffolds. Hematoxylin and eosin staining showed that the engineered blood vessels constructed by collagen/PLCL electrospun membranes formed relatively homogenous vessel-like tissues. Interestingly, Young's modulus for the engineered collagen/PLCL scaffolds was greater than for the gelatin/PCL scaffolds. Together, these results indicate that nanofibrous collagen/PLCL membranes with favorable mechanical and biological properties may be a desirable scaffold for vascular tissue engineering.Keywords: electrospinning, gelatin, collagen, polycaprolactone, poly(l-lactic acid-co-ε-caprolactone)